2006
DOI: 10.1016/j.physletb.2006.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Spinning gravitating skyrmions

Abstract: We investigate properties of self-gravitating isorotating Skyrmions in the generalized Einstein-Skyrme model with higher-derivative terms in the matter field sector. These stationary solutions are axially symmetric, regular and asymptotically flat. We provide a detailed account of the branch structure of the spinning solutions in the topological sector of degree one. We show that additional branches of solutions appear, as the angular frequency increases above some critical value, these "cloudy" configurations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 26 publications
1
63
0
Order By: Relevance
“…In contrast to the (conceptually simpler) spinning Q-ball solutions [34,35], for spinning Skyrmions the angular momentum J is a continuous parameter that can be arbitrarily small, so that they can rotate slowly and rotating solutions are continuously connected to static ones. The effects of gravity on these spinning Skyrmions has been studied by Ioannidou, Kleihaus and Kunz in [36], revealing, in particular, a number of configurations which do not have a flat space limit. No rotating BHs with Skyrme hair, however, have been constructed so far, presumably due to the complexity of the numerical problem.…”
Section: Jhep11(2017)037mentioning
confidence: 99%
“…In contrast to the (conceptually simpler) spinning Q-ball solutions [34,35], for spinning Skyrmions the angular momentum J is a continuous parameter that can be arbitrarily small, so that they can rotate slowly and rotating solutions are continuously connected to static ones. The effects of gravity on these spinning Skyrmions has been studied by Ioannidou, Kleihaus and Kunz in [36], revealing, in particular, a number of configurations which do not have a flat space limit. No rotating BHs with Skyrme hair, however, have been constructed so far, presumably due to the complexity of the numerical problem.…”
Section: Jhep11(2017)037mentioning
confidence: 99%
“…The EYM-dilaton theory admits also stationary spinning black holes, which is not very surprising, however, there are solutions which remain stationary and non-static even when their angular momentum vanishes 47 . Stationary spinning black holes have also been constructed in the dilaton-Gauss-Bonnet theory 48 , in the EinsteinSkyrme theory 49 , and in the conformally-coupled model (2) 50 . Here is a brief summary of some common features of the XX-th century hairy black holes.…”
Section: Xx-th Century Hairy Black Holesmentioning
confidence: 99%
“…On the other hand, in the context of application of the Skyrme model to the nuclear physics, the semiclassical quantization of angular momenta of spinning Skyrmion provides a natural way to identify the quantum numbers of a baryon [24]. Further, rotating Skyrmions persist when gravity is coupled to the usual Skyrme model [22]. It was observed that the structure of the corresponding branches of solution becomes more complicated, there are additional branches of solutions, which are not linked to the flat space Skyrmions or to the BM solutions [22].…”
mentioning
confidence: 99%